Al-Suyuti 's History Approach through his Book “Al-Shamareikh in the Science of History” - Shreiri, Saleem Mohammed ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2025)
This research that entitled (Al-Suyuti 's History Approach through his Book “Al-Shamareikh in the Science of History”) deals with the discussion of the principle of history in general and how the ancient Arabs used to document natural manifestations such as stars and crescents, or other great events in which humanity had a role, such as events like the year of the Elephant, the construction of Kaaba and so on, until Islam came, since then, they used the Prophet's Mohammed migration as a date which was the basis of Islamic history, and the matter has continued on that to this day. This was confirmed by the author of Al-Suyuti regarding the organization and historical sequence of the course of the date calendar, as he presented at the beginning of his talk, the principle of history, then the Hijri date, followed by the benefits of the history which were many and various and reviewed by days, months and years.